ON NEW FINDING OF MIRROR DORY ZENOPSIS NEBULOSA IN PETER THE GREAT BAY (JAPAN SEA) - L. N. Kim; P. G. Milovankin (Известия ТИНРО)
New finding of rare fish species mirror dory Zenopsis nebulosa in Peter the Great Bay (Japan Sea) is described.